Historia divina i historia naturalis w myśli Judy Loewa - Świeżyński, Adam (Humaniora. Czasopismo Internetowe, 2019)
The article is devoted to the presentation of the position of Judah Loew (Maharal) on the relationship between the scientific and religious view of the world. In his opinion, scientific and theological explanations are disproportionate and are located at various epistemic levels. Consequently, there can be no conflict between them. Each of them refers to a different history of their course, describing them as historia divina and historia naturalis. Although Loew clearly did not reject the path of scientific cognition, he expressed doubts about the effectiveness of contemporary scientific research due to the variety of scientific views and the multiplicity of the proposed solutions. The knowledge of religious revelation, which is, in his opinion, always reliable and accurate, is completely different. The consequence of the described position is his recognition that scientific knowledge remains potentially available to all people equally, regardless of their religion. However, there is a fundamental difference between Jews and other nations in terms of their internal, spiritual “equipment,” resulting from the experience, status and religious tradition of the Jews. Maharal’s position on the relationship between the natural science and Jewish theology seems to be an expression of religious exclusivity on the one hand and thus becomes close to the contemporary trends of religious fundamentalism, and on the other, expresses a strict separation of scientific and religious explanation of reality.